AI-Based Automation of the European Small Claims Procedure: Legal Framework Mapping - Maria Dymitruk (Revista Ítalo-Española de Derecho Procesal)
The paper explores current legal regulations regarding AI-based automation (full or partial) of the European Small Claims Procedure (ESCP). It analyzes European-level legislation, focusing on personal data protection (specifically Article 22 of the GDPR) and human rights (mainly Article 47 of the Charter of Fundamental Rights), while also mentioning the possibility of establishing a legal basis for ESCP automation in the national legal orders of EU Member States’ legal systems.